CAH Newborn Screening in India: Challenges and Opportunities - Aashima Dabas; Meenakshi Bothra; Seema Kapoor (MDPI AG, 2020)
Congenital adrenal hyperplasia (CAH) is a common treatable disorder which is associated with life-threatening adrenal crisis, sexual ambiguity, and/or abnormal growth if undiagnosed. Newborn screening is a cost-effective tool to detect affected babies early after birth to optimize their treatment and follow-up. Newborn screening however is in its nascent stage in India where it is not yet introduced universally for all babies. The following review briefly highlights the challenges (e.g., lack of universal screening, healthcare resources) and opportunities (e.g., reduction in morbidity and early correct gender assignment in females) associated with newborn screening for CAH in a large Indian birth cohort.